Tourism market recovery in the Maldives after the 2004 Indian Ocean tsunami - Carlsen, Jack; Hughes, Michael (The Haworth Press, 2007)
This paper will use a range of tourism data and a case study to examine the rates of recovery of ten source markets for the Maldives in the wake of the 2004 Indian Ocean tsunami. The market response and recovery rates for these ten markets varied significantly and the reasons for this will be explored. It is evident that a ‘one size fits all’ marketing strategy will not in itself be sufficient to achieve acceptable rates of recovery following a disaster. The strategies, opportunities and rates of market recovery experienced in the Maldives will provide useful insights for the marketing and monitoring of other destinations that have experienced a crisis or disaster.